Status-Dependent Vasotocin Modulation of Dominance and Subordination in the Weakly Electric Fish Gymnotus omarorum - Perrone, Rossana; Silva, Ana C. (Frontiers in Behavioral Neuroscience, 2018)
Dominant-subordinate status emerges from agonistic encounters. The weakly electric fish, Gymnotus omarorum, displays a clear-cut example of non-breeding territorial aggression. The asymmetry in the behavior of dominants and subordinates is outstanding. Dominants are highly aggressive and subordinates signal submission in a precise sequence of locomotor and electric traits: retreating, decreasing their electric organ discharge rate, and emitting transient electric signals. The hypothalamic neuropeptide arginine-vasotocin (AVT) and its mammalian homologue arginine-vasopressin, are key modulators of social behavior, known to adapt their actions to different contexts. By analyzing the effects of pharmacological manipulations of the AVT system in both dominants and subordinates, we show evidence of distinct status-dependent actions of AVT. We demonstrate an endogenous effect of AVT on dominants’ aggression levels: blocking the V1a AVT receptor induced a significant decrease in dominants’ attack rate. AVT administered to subordinates enhanced the expression of the electric signals of submission, without affecting subordinates’ locomotor displays. This study contributes a clear example of status-dependent AVT modulation of agonistic behavior in teleosts, and reveals distinctive activation patterns of the AVT system between dominants and subordinates.